2006
DOI: 10.1007/s00125-005-0111-5
|View full text |Cite
|
Sign up to set email alerts
|

The steel ball-bearing test: a new test for evaluating protective sensation in the diabetic foot

Abstract: Aims/hypothesis: The aim of the study was to assess a new steel ball-bearing test as a means of evaluating protective sensation in the diabetic foot. Methods: Subjects were enrolled for this study as follows: (1) 39 patients (mean age 61.3±9.7 years) with neuropathy and prior neuropathic ulcer (Group A); (2) 36 patients (mean age 63.7±10.1 years) with neuropathy without neuropathic ulcer (Group B); (3) 34 patients (mean age 52.1±10.4 years) without neuropathy (Group C); and (4) 21 healthy volunteers (mean age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…All the studies that evaluated its association with DFU development , active or recently healed DFU , active or past DFU and DFU history achieved statistical significance. In contrast, only one study (out of three) for the prediction of foot ulcer recurrence or re‐ulceration observed an association .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…All the studies that evaluated its association with DFU development , active or recently healed DFU , active or past DFU and DFU history achieved statistical significance. In contrast, only one study (out of three) for the prediction of foot ulcer recurrence or re‐ulceration observed an association .…”
Section: Resultsmentioning
confidence: 92%
“…From the 71 included studies, 24 studies evaluated the association of specific variables with DFU development (Table ), 14 studies with DFU recurrence or re‐ulceration (Table ), 15 studies with active or recently healed DFU (Table ), 8 studies with active or past DFU history (Table ) and 10 studies with DFU history (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[77] More sophisticated, not widely used alternative tests of protective sensation include the tactile circumferential discriminator [78] and the steel ball-bearing test. [79] Finally, a new simple test measures sweat production by color change of an indicator test applied on the plantar aspect of the foot, thereby additionally evaluating foot skin dryness. [21] In addition, the clinician should meticulously examine the foot for evidence of increased risk.…”
Section: The Diabetic Foot In Renal Failure: Examination and Risk Estmentioning
confidence: 99%
“…Clinical examination encompassing sensory and motor modalities remains the cornerstone of diagnosis in realworld settings [1,3]. Efforts to improve the diagnosis of DSPN and facilitate larger-scale patient screening have resulted in the development of new tests [3,4], such as the indicator test for sudomotor function (Neuropad [5]), the steel ball-bearing test [6], the automated nerve conduction study of the sural nerve [7,8], VibraTip [9,10], among others.…”
Section: Introductionmentioning
confidence: 99%